Peran Bimbingan dan Konseling Terhadap Tingkat Emosional Tenaga Kerja Rumah Sakit Jiwa - Halifah khairunisa; Arya Ramadhan; Iryne Ruzea; Putri Tri Rizki; Muhammad Rai Farhan; Affan Yusra (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The purpose of this study was to determine the role of guidance and counseling on the emotional level of the workforce in the Mental Hospital. The subjects of this study were nurses, psychiatrists, psychologists and other mental hospital staff. The technique we use in this research is literature review. Workers in mental hospitals do not take care of people who are mentally fine, which certainly makes their emotional level disturbed too. Workers in mental hospitals are expected to be able to control their emotions because working in mental hospitals has become a decision that workers make, so they are required to work professionally